IMPROVING QUALITY OF LIFE AFTER HIP REVISION ARTHROPLASTY - Pop, Tudor Sorin; Zuh, Sandor-Gyorgy; Hidi, Margit; Vass, Attila; Gergely, Istvan (European Scientific Journal, ESJ, 2015)
Nowadays the number of primary arthroplasties is growing and revision arthroplasty is becoming increasingly necessary. In this study we intend to examine the effectiveness of arthroplasties and assess the quality of life. We included 35 patients with revision arthroplasty and 35 primary hip arthroplasty patients who had surgery between 2011 and 2012 in the study. To examine the results we used the modified Harris hip score and the Rosser matrix, which was completed before surgery and 2-3 years after the procedure. We observed a statistically significant improvement: from 34 preoperative Harris hip score 75 at the 2 years postsurgery assessment and 72 at the 3 years postoperative assessment (p <0.0001). Significant improvements were also registered when assessing the health state with the Rosser matrix. The effect for the Harris score had a value of 2.06 which testifies the revision surgery has a high effectiveness. This means that with this kind of procedures dramatic improvement in quality of life can be achieved.